THE RELATIONSHIP BETWEEN DEPRESSION AND LIFE SATISFACTION AMONG UNIVERSITY UNDERGRADUATES - Ejike .H Mgbenkemdi; Ifeatu. A Okafor (ESUT JOURNAL OF SOCIAL SCIENCES, 2021)
This study investigated depression as a correlate of life satisfaction among students of Enugu State University of Science and Technology (ESUT) using a simple random sampling technique. A total of 70 participants comprising 34 male and 36 female students from the Department of Psychology with ages between 16-20 years, with a mean age of 17.92 and a standard deviation of 1.26 years were selected for the study. Self-Rating Depression scale (SRDS Zung (1965). While Life Satisfaction Index-Short Form (LIS-SF) was developed by Barrett and Murk (2009) A correlation research design was adopted for data collection, while the Pearson Moment Correlation Coefficient was applied to analyze the data. The findings showed that those who are depressed are not satisfied with life.  The participants showed an increase in depression and a decrease in life satisfaction. Therefore, the present study shows that with the high level of depression the students will not be satisfied with life. The results have also implications for clinical practices especially as it relates to counselling.